Solar radiation influence onto the spent nuclear fuel dry storage container - Alyokhina, S.V.; Kapuza, S.S.; Kostikov, A.O. (Вопросы атомной науки и техники, 2018)
In the paper the solar influence on the thermal state of storage container with spent nuclear fuel is investigated by numerical simulation. Thermal simulation for the single container and for the group of containers was carried out. The daily temperature fluctuations of the concrete container surface under maximum solar influence were calculated. The absence of solar radiation influence onto the spent fuel assemblies inside storage container is shown. Шляхом чисельного моделювання досліджено вплив сонячного випромінювання на тепловий стан контейнера з відпрацьованим ядерним паливом. Теплові дослідження виконані для окремо розташованого контейнера та для групи контейнерів. Обчислені добові коливання температури бетонної поверхні контейнера при максимальному сонячному навантаженні. Показано відсутність впливу сонячного випромінювання на відпрацьовані паливні збірки в середині контейнера зберігання. Путем численного моделирования исследовано влияние солнечного излучения на тепловое состояние контейнера с отработавшим ядерным топливом. Тепловые исследования выполнены для отдельно расположенного контейнера и для группы контейнеров. Вычислены суточные колебания температуры бетонной поверхности контейнера при максимальной солнечной нагрузке. Показано отсутствие влияния солнечного излучения на отработавшие топливные сборки в середине контейнера хранения.